Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah terhadap Tingkat Profitabilitas pada Bank Syariah (Studi pada Bank Syariah yang Terdaftar di BI Periode 2015-2017) - Widya Febryari Anita; Ahmad Nawawi; Diana Putri (Accounthink : Journal of Accounting and Finance, 2022)
The purpose of this study is to determine the effect of mudharaba financing and musharaka financing on profitability of the Sharia Bank in the 2015-2017 period. The sampling technique used was purposive sampling which then obtained 3 Islamic banks that were suitable to be sampled in this study.The research method used is quantitative descriptive method. Data analysis  techniques in this study include descriptive statistic analysis, classic assumption test, multiple linear regression analysis, statistical analysis coefficient of determination, and hypothesis test using partial significance test (t-test) and simultant significance test (f-test). This study used SPSS version 25 software to process the data. The results showed that mudharabah financing partially did not affect the level of profitability with a tcount of 1.138 <ttable 2.035 with significance of 0.263> 0.05. Musyarakah financing partially affects the profitability rate with a tcount of -5.865 <-ttable of -2.035 with a significance of 0.000 <0.05. Simultaneously mudharabah financing and musyarakah financing affect the level of profitability with a fcount value of 17.937> ftabel 3.28 with a significance of 0.000 <0.05.